Gratian the theologian - Wei, John C. (Washington, D.C The Catholic University of America Press, 2016)
Gratian the author and biblical exegete -- Gratian and his book(s) -- The Bible -- Gratian the penitential theologian -- The practice and theory of penance -- Gratian on penance -- Critiquing and correcting the scholastics -- From penitential theology to the canon law of magic -- Gratian, a theologian of the sacraments and liturgy? -- Gratian, a sacramental theologian? -- Gratian, a liturgist?
Literaturverzeichnis: Seite 311-336
Keywords: Gratian -- active 12th century; Penance -- History of doctrines -- Middle Ages, 600-1500; Theology -- History -- Middle Ages, 600-1500